Pesticides and Chemical Fertilizer are not Negatively Impact the Diversity of Entomopathogenic Fungi on Rice Plant in Malang Indonesia - Rose Novita Sari Handoko; Aminudin Afandhi; Amin Setyo Leksono; Mufidah Afiyanti; Tri Suyono (Indonesian Journal of Environment and Sustainable Development, 2022)
The conventional system of rice plantation has been applied in Malang, Indonesia. Standard chemical fertilizer and pesticide application were used in this field. Soil samples in rhizosphere of rice plantation showed the existence of several entomopathogenic fungi including Penicillium sp, Aspergillus sp, Trichoderma sp and some unidentified fungi. The diversity value also demonstrated a medium diversity. We conclude that an application of pesticides and chemical fertilizer according to recommended practices, are not negatively affect the diversity of entomopathogenic fungi. Aspergillus sp and Penicilium sp can cause death against Spodoptera litura.